Persepsi Orang Tua Siswa tentang Pengaruh Bullying di SDS ST. Antonius Medan - Wilda Anicheta Sinaga; Intan Silvia Mardiani Gulo; Rebecca Adelia Situmorang; Solida FY Sihombing; Debora Sitindaon; Sartika Siahaan (Journal Innovation In Education, 2024)
This study aims to examine the influence of bullying on the dynamics of debates between parents of students at SDS st Antonius Medan. Bullying in the school environment can have broad social impacts, including the involvement of parents in discussions and debates regarding handling the problem. Through a qualitative approach, this study collected interview data and participatory observations.